High Prevalence and Overexpression of Fosfomycin-Resistant Gene fosX in Enterococcus faecium From China - Xin, Ling; Xu, Xiaogang; Shi, Qingyu; Han, Renru; Wang, Jue; Guo, Yan; Hu, Fupin (Frontiers in Microbiology, 2022)
Enterococci is one of the main causes of gastrointestinal tract infections in the healthcare system, and can develop resistance to fosfomycin through plasmid or chromosomally encoded fosfomycin resistance genes. To investigate the mechanisms of fosfomycin resistance, a total of 4414 clinical isolates of non-replicated clinical enterococci collected from 62 hospitals in 26 provinces or cities in China were tested. Antibiotic susceptibility testing, detection of fosfmycin resistance genes, and cloning of fosX gene were done. The PFGE, MLST, qRT-PCR, and next genome sequencing were carried out. The results revealed that the fosfomycin-resistant rate of enterococci was 3.5% (153/4414), and the major resistance mechanism was fosX (101/153) and fosB (52/153) genes. The fosX gene could increase 4- fold of fosfomycin MIC in Enterococcus faecium BM4105RF transformants, and the results of PFGE showed the 101 E.faecium carrying fosX were grouped into 48 pulse types. The multilocus sequence typing identified ST555 as the vast majority STs, mostly distributed in Shanghai, China. Furthermore, the fosX gene expression was strongly related to the fosfomycin-resistant levels of enterococci. The present study was the first to describe the high prevalence presence of fosX gene in E.faecium from China.